The Use of Interactive Posters to Enhance Vocabulary Acquisition Among Seventh Grade Students At Smp Negeri 1 Hutabargot - Desnita; Mahrani; Yulia Rizki Ramadhani (Yayasan Perguruan Kampus, 2025)
This research study conducted based on the problem in the students’ vocabulary in English. The aim is to know the enhancing of students’ vocabulary acquisition by using interactive posters. The Class Action Research (CAR) used to investigate the students’ vocabulary start from pre-test until post-test. There are 32 students as sample. The multiple-choice written test gave to students as instrument and analyzed based on statistical formula of CAR. The research finding showed that the means score of students’ vocabulary acquisition was 47.4 in pre-test, 68 in post-test cycle 1 and 83 in cycle 2. The improvement from pre-test to post-test was 74.7% and the KKM achievement was 87.5%. Based on the finding, the interactive poster significantly effects to the students’ vocabulary acquisition. This kind of teaching media was recommended to be applied in teaching and learning process of vocabulary mastery in English language lesson.